Efektivitas Penggunaan Media Manipulatif Clothespin dalam Meningkatkan Kemampuan Motorik Halus Anak Usia Dini 4-5 Tahun - Amalia Monoarfa; Amelia Daaliwa; Cindawati Pakaya; Triassetiawaty Dade; Annisa Fahmi Mannasai; Sri Yulan Umar (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This research, conducted at TK Al-Irsyad Al-Islamia in Gorontalo, Indonesia, investigated the effectiveness of using clothespins as a manipulative media to enhance fine motor skills in young children aged 4-5 years old. Initial observations revealed that some children exhibited underdeveloped fine motor skills, struggling with activities like coloring, pasting, and drawing. The research employed a descriptive qualitative approach, utilizing survey methods and document analysis. Findings indicated that the use of clothespins as a manipulative tool proved effective in improving fine motor skills. Children successfully matched the number of clothespins with numbers on a cardboard and stood them upright, demonstrating improved fine motor control. The research recommends the regular use of clothespins as a manipulative aid in learning activities to enhance fine motor skills in young children. Further research is needed to explore the effectiveness of using clothespins with varying age groups and levels of difficulty. It is hoped that this research will inspire educators to utilize creative and engaging manipulative media in their teaching practices, thereby fostering children's interest and motivation in learning.